Pharmacokinetics of plasma‐derived C1‐esterase inhibitor after subcutaneous versus intravenous administration in subjects with mild or moderate hereditary angioedema: the PASSION study. Issue 6 (24th November 2013) - Martinez‐Saguer, Inmaculada; Cicardi, Marco; Suffritti, Chiara; Rusicke, Eva; Aygören‐Pürsün, Emel; Stoll, Hildegard; Rossmanith, Tanja; Feussner, Annette; Kalina, Uwe; Kreuz, Wolfhart
<x xml:space="preserve">Abstract</x> Background Hereditary angioedema (HAE) is a rare disease caused by C1‐esterase inhibitor (C1‐INH) deficiency, characterized by periodic attacks of acute edema affecting subcutaneous (SC) tissues and mucous membranes. Human C1‐INH concentrate given intravenously (IV) is effective and safe, but venous access may be difficult. We compared SC and IV administration of human pasteurized C1‐INH concentrate with respect to pharmacokinetics, pharmacodynamics, and safety. Study Design and Methods This was a prospective, randomized, open‐label, crossover study. Twenty‐four subjects with mild or moderate HAE were randomly assigned during an attack‐free interval to receive 1000 units of human pasteurized C1‐INH concentrate IV or SC. Plasma levels of C1‐INH activity and antigen, C4 antigen, cleaved high‐molecular‐weight kininogen (clHK), and C1‐INH antibodies were measured. Results The mean relative bioavailability of functional C1‐INH after SC administration was 39.7%. Maximum C1‐INH activity after SC administration occurred within 48 hours and persisted longer than after IV administration. C4 antigen levels increased and clHK levels decreased after IV and SC administration, indicating the pharmacodynamic action of C1‐INH. The mean half‐life of functional C1‐INH was 62 hours after IV administration and 120 hours after SC administration (p = 0.0595). C1‐INH concentrate was safe and well tolerated when administered via both routes. As expected, SC administration resulted in a higher incidence of injection site reactions, all of which were mild. Conclusion With a relative bioavailability of 39.7%, SC administration of human pasteurized C1‐INH yields potentially clinically relevant and sustained plasma levels of C1‐INH and is safe and well tolerated.